DAKWAH ISLAMIYAH BERKENAAN IDUL FITHRI MEMBANGUN IDENTITAS DIRI - Parinduri, Luthfi; Alam, Hermansyah; Masri, Mahrizal; Napid, Suhardi (Universitas Islam Sumatear Utara, 2024)
Eid al-Fitr is often used as an important momentum for the Muslim community to stay in touch and celebrate victory after a month of fighting against our own desires, which are the biggest enemies in our lives. Our desires have led us to an excessive love of wealth, luxury, position and power. From a sociological perspective, our society today seems to be experiencing what is called anomie. Anomie is a critical condition in society resulting from social change where old norms/values fade, but new norms/values that will replace them have not yet been formed. Thus, in school community life, it is as if there are no norms or values. The Oxford Dictionary connects the meaning of integrity with a person's personality, namely being honest and complete. There are also those who define integrity as moral excellence and equate integrity with